Navigating the new normal: A study on Indonesian travelers' willingness to pay more post-pandemic using the theory of planned behavior - Lianna Wijaya; Kah Choon Ng; Pardomuan Robinson Sihombing; Tiurida Lily Anita (Jurnal Manajemen dan Pemasaran Jasa, 2024)
One of the industries that have been most negatively impacted by the COVID-19 pandemic is the tourism industry, which has seen a major drop in international travel, an increase in domestic travel, and changes in consumer behavior. This study aims to study the intention of people to travel and the willingness of people to pay more for safety and precautions when traveling. These studies have addressed the matter of the lack of research on changes in the behavior and patterns of travelers.  A total of 239 valid questionnaires were collected using an online survey with a purposive sampling technique. The PLS-SEM is employed to test the model. The theory of planned behavior (TPB) as a conceptual framework. Perceived risk influences the attitude of Indonesian Tourists in post-pandemic but has no influence on perceived behavior control. Attitude has a positive and significant direct influence on intention to travel and willingness to pay more. Perceived behavior control influences on intention to travel but no influence on willingness to pay more. Lastly, the intention to pay more does not influence willingness to pay more. The empirical findings have the potential to enhance the implementation of safety precautions in tourism services and the formulation of efficient strategies to revive tourism. This study substantially contributes to the body of knowledge because presented empirical proof of travel behavior patterns in Indonesia in the post-pandemic.